The Euphoria Effect of SCM Activities with SCM Perfomance on SMEs in Indonesia - Fatimah, Tiara; Febiola, Windi; Masnita, Yolanda (Manajemen Bisnis Kompetensi, 2018)
This study examines the influence of customer relationships, supplier relationships, and internal relationships with supply chain performance in the SMEs sector. Data were collected by questionnaire survey from 114 SMEs businesses in food, beverages and clothing. Structural Equation Modeling (SEM) approach was used to test the hypotheses. The results provide support for the proposed hypotheses. The results indicate that there is an effect of the Customer link towards Supply Chain Performance, There is an effect of Supplier Linkage towards Supply Chain Performance, and there is an effect from Internal Linkage toward Supply Chain Performance. So that this study can bring benefits to improve the performance of SMEs supply chains. Keywords: Supply Chain Management, Customer Linkage, Supplier Linkage, Supply Chain Performance, SMEs